1996
DOI: 10.1046/j.1365-2249.1996.d01-792.x
|View full text |Cite
|
Sign up to set email alerts
|

T helper type-1 (Th1)/Th2 profiles of peripheral blood mononuclear cells (PBMC); responses to antigens of Chlamydia trachomatis in subjects with severe trachomatous scarring

Abstract: SUMMARYIncreased stimulation of Th2 cytokines may contribute to the development of persistent ocular chlamydial infection, resulting in the blinding pathological changes of trachoma. Proliferation and cytokine production profiles of PBMC in response to stimulation with antigens of Chlamydia trachomatis were compared in 30 patients with severe conjunctival scarring due to trachoma and in 30 age-, sex-and location-matched controls. Interferon-gamma (IFN-°) and IL-4 were detected at the single-cell level by ELISP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
95
2
1

Year Published

1997
1997
2009
2009

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 129 publications
(106 citation statements)
references
References 25 publications
8
95
2
1
Order By: Relevance
“…Therefore, our results suggest that failure to mount an effective Thl response to eliminate ReAtriggering bacteria might be a relevant pathogenetic factor in ReA, as has also been suggested for severe trachomatous scarring after infection of the eye with C trachomatis (50). The presence of HLA-B27 might be more relevant for chronic courses and for the development of spondylarthropathy-specific features than for the pathogenesis of acute ReA (7,8,20).…”
Section: Discussionmentioning
confidence: 51%
“…Therefore, our results suggest that failure to mount an effective Thl response to eliminate ReAtriggering bacteria might be a relevant pathogenetic factor in ReA, as has also been suggested for severe trachomatous scarring after infection of the eye with C trachomatis (50). The presence of HLA-B27 might be more relevant for chronic courses and for the development of spondylarthropathy-specific features than for the pathogenesis of acute ReA (7,8,20).…”
Section: Discussionmentioning
confidence: 51%
“…High ex vivo IL10 production by lymphocytes from patients with scarring trachoma (TS) has also been observed. 16 Evidence from a twin study suggested that genetic variation influences the host immune response to trachoma. 17 We have identified associations between trachomatous scarring and HLA class I and II alleles, and with single-nucleotide polymorphism (SNPs) at the TNFa and IL10 loci in Gambians in previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…We previously found that the mouse strain that produces higher organism-driven IFN-␥ production shows significantly more resistance to chlamydial infection (10,17) and that IFN-␥ gene knockout (KO) mice, IL-12 KO mice, and IL-18 KO mice exhibit much more serious diseases when compared with wild-type mice (27,28). Studies by other groups also demonstrated the extreme importance of IFN-␥ and Th1 immune responses in host defense against chlamydial infection (14,22,23,25). Dendritic cells (DC) have been shown to be the most efficient APC in priming T cells.…”
mentioning
confidence: 99%